Research of a new security mechanism on energy internet - Yongmei, Luo; Ying, Wang; Gen, Li (Indian Journal of Power and River Valley Development, 2022)
The sustainable exploitation and utilization of new energy is the basis of future development of mankind. As the core infrastructure for the efficient and secure utilization of renewable energy sources, the energy internet is an important strategic resource and an embodiment of the comprehensive national strength. This paper presents a new security mechanism based on Trusted Platform Module (TPM). Fistly, the analysis of the structure of the energy internet is discribed from two aspects of logic structure and network topological structure. Sencondly the existing research methods of energy internet security are divided into three classes: security demand-driven method, security model-driven method and system-theoretic method. The vulnerability of isolated research and lack of integrated solution is found out. Then the new security mechanism is propossed and the security model along with the consuming layer protocol are put forward. Finally the security analysis is processed. The results show that the new security mechanism can satisfy the security requirements of energy internet.